Sentiment versus mood: A conceptual and empirical investigation - Albert Rapp (Journal of Capital Markets Studies (JCMS), 2019)
Purpose - The purpose of this paper is to investigate whether sentiment and mood, which are distinct theoretical concepts, can also be distinguished empirically. Design/methodology/approach - Using a sample of German small-cap stocks and linear techniques, the effect of sentiment and mood on short-term abnormal stock return following earnings announcements is tested separately. Findings - Mood tends to be a positive factor in predicting short-term abnormal stock return, as its biologically based impact uniformly affects the risk aversion of all market participants. Notably, negative mood influences stock return significantly negatively. Sentiment is no factor, however, as its cognitively based impact affects only unsophisticated investors, namely, their cash-flow expectations. Research limitations/implications - As the sample is restricted to small-cap stocks from a single stock market and only two proxies of sentiment and mood, respectively, are used, the findings should be generalized with caution. Future research might investigate other markets and employ different proxies of sentiment and mood. Practical implications - Market participants should be aware of the different effect of sentiment and mood on stock return and adjust investment strategies accordingly. Social implications - As sophisticated investors are likely to profit from the irrational behavior of unsophisticated investors, who are prone to sentiment, the financial literacy of retail investors should be enhanced. Originality/value - This paper is unique in distinguishing between sentiment and mood, both theoretically and empirically. Such distinction was largely ignored by related past research.
Keywords: 330; Mood; Sentiment; Cognitive bias; Arbitrage; Post-earnings announcement drift (PEAD)